Perception of officers in work safety protocols to achieve zero accidents at PT. Paramitha Build Means - Alelga, Elsa; Susilawati, Susilawati; Arrazy, Syafran (Science Midwifery, 2025)
The high rate of occupational accidents indicates that the implementation of Occupational Safety and Health (OSH) in the construction sector still needs to be strengthened, including at the PT. Paramitha Bangun Sarana (Soci Mas) project, where worker compliance with the use of personal protective equipment (PPE) and standard operating procedures (SOPs) remains low. This study aims to describe the implementation of safety protocols and the achievement of the zero-accident program at the project site. A descriptive quantitative method was applied using a total sampling of 50 field workers. Data were collected through questionnaires and observations. Frequency distribution results show that most respondents were aged 18–33 years (82%), male (94%), and high-school graduates (82%). The level of OSH protocol perception was very good, with 94% of respondents agreeing and 6% strongly agreeing on the optimization of safety protocols. Zero-accident achievement was also high, indicated by 94% agreeing and 4% strongly agreeing with the program's application. These findings confirm that consistent application of OSH protocols, strong management support, and a solid safety culture can create a safe work environment, support the realization of zero-accident targets, and contribute to Sustainable Development Goal (SDG) 8 on decent work and economic growth.